2022
DOI: 10.7150/jca.77768
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of secondary cancer in nasopharyngeal carcinoma patients after radiotherapy

Abstract: Purpose: To identify risk factors of secondary cancer in nasopharyngeal carcinoma (NPC) patients after radiotherapy. Materials and methods:The data of NPC patients with secondary cancer were extracted from the Surveillance, Epidemiology, and End Results database from 2004 to 2016. Univariate and multivariate logistic regression analysis was performed to identify risk factors of secondary cancer. Risk factors selected from the multivariable logistic regression analysis were used to build a predicting model. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Although several studies have assessed the age at diagnosis as a continuous variable of survival and suggested that age at diagnosis is a continuous independent prognostic factor, [ 18 , 19 ] it is difficult to use age at diagnosis as a continuous variable in clinical practice. Therefore, oncologists require a more appropriate cutoff value to assess prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have assessed the age at diagnosis as a continuous variable of survival and suggested that age at diagnosis is a continuous independent prognostic factor, [ 18 , 19 ] it is difficult to use age at diagnosis as a continuous variable in clinical practice. Therefore, oncologists require a more appropriate cutoff value to assess prognosis.…”
Section: Discussionmentioning
confidence: 99%